Research progress of fully biodegradable and antimicrobial materials applied in personal protective equipment - Jingqiu Feng#; Yiwen Zeng#; Zhe Li#; Gaoling Huang; Dong Liang; Enchi Zhou; Chunhong Zhang; Dan Li; Linfang Mo (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2022)
Due to the outbreak of COVID-19, a large number of disposable personal protective equipment (PPE) wastes were generated. It has caused great harm to the ecological environment, and even in the future may endanger human health. Therefore, it is of great significance to research biodegradable materials that can be used in the field of medical protective equipment. This article reviews the application of biodegradable materials in personal protective equipment. First of all, the classification, characteristics, and general application of biodegradable materials are described. Then, the application of biodegradable antibacterial materials, which can improve the degradability, antibacterial, and comfort of medical protective articles, is analyzed. Finally, the significance and challenges are discussed, and some prospects in this field are put forward.